Patient-reported outcomes of adults with congenital heart disease from eight European countries: scrutinising the association with healthcare system performance. (1st August 2019) - Van Bulck, Liesbet; Luyckx, Koen; Goossens, Eva; Apers, Silke; Kovacs, Adrienne H; Thomet, Corina; Budts, Werner; Sluman, Maayke A; Eriksen, Katrine; Dellborg, Mikael; Berghammer, Malin; Johansson, Bengt; et al.
Abstract: Background: Inter-country variation in patient-reported outcomes of adults with congenital heart disease has been observed. Country-specific characteristics may play a role. A previous study found an association between healthcare system performance and patient-reported outcomes. However, it remains unknown which specific components of the countries' healthcare system performance are of importance for patient-reported outcomes. Aims: The aim of this study was to investigate the relationship between components of healthcare system performance and patient-reported outcomes in a large sample of adults with congenital heart disease. Methods: A total of 1591 adults with congenital heart disease (median age 34 years; 51% men; 32% simple, 48% moderate and 20% complex defects) from eight European countries were included in this cross-sectional study. The following patient-reported outcomes were measured: perceived physical and mental health, psychological distress, health behaviours and quality of life. The Euro Health Consumer Index 2015 and the Euro Heart Index 2016 were used as measures of healthcare system performance. General linear mixed models were conducted, adjusting for patient-specific variables and unmeasured country differences. Results: Health risk behaviours were associated with the Euro Health Consumer Index subdomains about patient rights and information, health outcomes and financing and access to pharmaceuticals. Perceived physical health was associated with the Euro Health Consumer Index subdomain about prevention of chronic diseases. Subscales of the Euro Heart Index were not associated with patient-reported outcomes. Conclusion: Several features of healthcare system performance are associated with perceived physical health and health risk behaviour in adults with congenital heart disease. Before recommendations for policy-makers and clinicians can be conducted, future research ought to investigate the impact of the healthcare system performance on outcomes further.